The need for an independent law reform commission in Malaysia: a comparative study between UK, India, New Zealand and Australia / Ahmad Nabilimran Ahmad Halimi, Ahmad Hazimi Abd Rahman and Dayang Sharlina Datu Basrun - Ahmad Halimi, Ahmad Nabilimran; Abd Rahman, Ahmad Hazimi; Datu Basrun, Dayang Sharlina (2013)
The formation of a law reform commission has been an issue and a concern to both the people and the government throughout the world in achieving contemporaneous laws that are relevant to meet the needs of society. In order to deal with this issue, independent Law Commissions have been established in most of the Commonwealth countries with the main objective of having a law that is up to date, fair, just and easily accessed by the people. Unfortunately in Malaysia, there is no independent Law Commission. Malaysia has only two law reform agencies namely the Malaysian Law Reform Committee (MLRC) and Law Reform and Revision Division (LRRD). Nevertheless, these two reform agencies fall under the same ministry department that is the Prime Minister's Department. Subsequently, these committees are not independent from the government. This amounts to limited jurisdiction and powers granted to MLRC and LRRD. The independency of the law reform entities is vital to ensure the development of law reform. Also, it is about time that these committees are converted into an independent law commission that has more powers to conduct its own research and review laws with or without the directions from the Government or the Attorney General. Thus, this project paper provides a specific analysis on Malaysia's current law reform mechanisms. On top of that, this project paper also provides a comparative research on the salient features of the foreign law reform commissions that are progressive in their operation namely in UK, India, Australia and New Zealand.